2017
DOI: 10.1002/jbm.a.35993
|View full text |Cite
|
Sign up to set email alerts
|

In vivostudy on the biocompatibility of chitosan–hydroxyapatite film depending on degree of deacetylation

Abstract: Chitosan, produced from chitin, is one of the polymers with promising applications in various fields. However, despite diverse research studies conducted on its biocompatibility, its uses are still limited. The main reason is the degree of deacetylation (DOD), which represents the proportion of deacetylated units in the polymer and is directly correlated with its biocompatibility property. In this article, the in vivo biocompatibility of three chitosan-hydroxyapatite composite films composed of chitosan with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…Younes et al demonstrated bladder carcinoma cells treated with CS (> 50% DA) significantly reduced viability after 24 h, suggesting CS cytotoxicity is directly related to its DA which can impact proliferation [ 45 ]. This effect may also be isolated to in vitro experimental conditions; previous studies have shown CS to be non-toxic in vivo, as its biodegradation products could be cleared through metabolic pathways [ 46 ]. Residual HFIP from the electrospinning process may also contribute to the observed cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Younes et al demonstrated bladder carcinoma cells treated with CS (> 50% DA) significantly reduced viability after 24 h, suggesting CS cytotoxicity is directly related to its DA which can impact proliferation [ 45 ]. This effect may also be isolated to in vitro experimental conditions; previous studies have shown CS to be non-toxic in vivo, as its biodegradation products could be cleared through metabolic pathways [ 46 ]. Residual HFIP from the electrospinning process may also contribute to the observed cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Bojar et al discovered that trabecular bone formation around a CS/β‐tri‐calcium phosphate with a 95% DD bone graft with no the inflammatory response. However, Jeong et al reported that CS with a higher DD value results in a high level of inflammation in skin cells. Heretofore, there is still no consistent conclusion on the biological effect of CS with DDs.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin has a lower biocompatibility than CS, because it contains a high amount of N-acetyl-D-glucosamine. 12 On the other hand, a DD value above 50% implies that the copolymer is CS due to the higher ratio of D-glucosamine units. 13 Recently, utilizing CS with different DDs for drug adsorption has attracted extensive research attention.…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting observation, and so should be factored into the rational for novel wound healing devices. However, it is suggested that this observation may be unique to in vitro experimentation, as prior studies using chitosan observed negligible toxic effect in vivo, linked with metabolic clearance of biodegradation products (Kean and Thanou, 2010;Jeong et al, 2017).…”
Section: Electrospun Polymers With Added Therapeutics For Scar Treatmentmentioning
confidence: 98%